AEROBIC AND ANAEROBIC EXERCISE TO ENHANCE PHYSICAL FITNESS OF CHRONIC KIDNEY DISEASE PATIENTS ON HEMODIALYSIS: A LITERATURE REVIEW - Masita Widiyani; Tintin Sukartini; Abu Bakar (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Chronic kidney disease is a condition where kidney has declining its function. It can cause a loss of physical capacity characterized by decreased body fitness, muscle strength and muscle endurance. Exercise programs to overcome the problem are still not common in dialysis clinics but there are several studies on exercise programs that have a positive effect on hemodialysis patients. Objectives: This study aimed to review aerobic and anaerobic exercise to enhance physical fitness for chronic kidney disease patients on hemodialysis. Design: The study design used was systematic review with using The Center for Review and Dissemination for writing guideline and the Joanna Briggs Institute Guideline for assessing the quality of summarized studies. Data Sources: Search for articles accessed through database, such as ProQuest, Scopus, Science Direct, SAGE, and PubMed with keywords: Chronic kidney disease, aerobic exercise, anaerobic exercise, physical function and hemodialysis. The literature was published 2015-2021. Review Methods: Joanna Briggs Institute Guidelines was used to assess the quality of the summarized studies. The presentation of the data will be done using descriptive techniques. Results: The result of this systematic review shows that both aerobic and anaerobic exercise have a significant result for chronic kidney disease patient who undergo hemodialysis therapy. But aerobic exercise had a long-term impact for patients than anaerobic exercise. Combination of aerobic (ergometer cycle) and anaerobic exercise (resistance training exercise) also show a significant effect for physical fitness. The mechanism for enhancing physical fitness is done by strengthen the body muscle. The side effect of exercise is found minimum in most of study. Conclusion: The combination of cycle ergometer exercise and resistance training exercise is one of the best exercises. The exercise could enhance the physical fitness by strengthen the muscle. The exercise could be done home based or intradialytic, but some articles state that intradialytic exercise is better than home based exercise.